2007
DOI: 10.1093/eurheartj/ehm545
|View full text |Cite
|
Sign up to set email alerts
|

Prasugrel achieves greater and faster P2Y12receptor-mediated platelet inhibition than clopidogrel due to more efficient generation of its active metabolite in aspirin-treated patients with coronary artery disease

Abstract: In aspirin-treated subjects with coronary artery disease, prasugrel 60/10 mg provides faster onset and greater inhibition of P2Y(12) receptor-mediated platelet aggregation than clopidogrel 600/75 mg, because of greater and more efficient generation of the active metabolite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
270
1
14

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(290 citation statements)
references
References 31 publications
5
270
1
14
Order By: Relevance
“…Similarly, the ability of prasugrel to provide platelet inhibition is sensitive to the timing of its administration relative to cangrelor infusion such that it is recommended that prasugrel loading dose is administered 30 minutes before the cessation of cangrelor infusion [42]. This is because of two key considerations: (1) the distribution half-lives of both clopidogrel and prasugrel active metabolites are short (30 to 60 minutes) so that therapeutic levels of the active metabolites decline rapidly following absorption and metabolism of the parent drug [43][44][45][46]; and (2) these active metabolites are unable to bind to the platelet P2Y 12 receptor whilst cangrelor is bound to the receptor [47,48]. Consequently, if the levels of the active metabolites fall to subtherapeutic concentrations before cangrelor has dissociated from the platelet P2Y 12 receptors then no effective platelet inhibition will ensue.…”
Section: Interaction With Oral P2y 12 Inhibitorsmentioning
confidence: 99%
“…Similarly, the ability of prasugrel to provide platelet inhibition is sensitive to the timing of its administration relative to cangrelor infusion such that it is recommended that prasugrel loading dose is administered 30 minutes before the cessation of cangrelor infusion [42]. This is because of two key considerations: (1) the distribution half-lives of both clopidogrel and prasugrel active metabolites are short (30 to 60 minutes) so that therapeutic levels of the active metabolites decline rapidly following absorption and metabolism of the parent drug [43][44][45][46]; and (2) these active metabolites are unable to bind to the platelet P2Y 12 receptor whilst cangrelor is bound to the receptor [47,48]. Consequently, if the levels of the active metabolites fall to subtherapeutic concentrations before cangrelor has dissociated from the platelet P2Y 12 receptors then no effective platelet inhibition will ensue.…”
Section: Interaction With Oral P2y 12 Inhibitorsmentioning
confidence: 99%
“…In patients scheduled for percutaneous coronary intervention, inhibition of platelet aggregation is significantly greater in patients receiving prasugrel than those receiving clopidogrel, both at 6 h after a loading dose (mean ± SD, 75 ± 13% vs 32 ± 21%) and during maintenance doses (61 ± 18% vs 46 ± 21%) [17]. Although prasugrel metabolism is less influenced by known cytochrome genetic polymorphisms, a large variability in biological responsiveness is still present [8], and HPR can be present in up to 25% of ACS patients who in turn showed an increased incidence of ischaemic events at one month on from percutaneous coronary intervention (PCI) [18]. Therefore, platelet function testing, which has been shown to be useful for the prediction of both ischemic and bleeding events in clopidogrel-treated patients, could also be clinically relevant in prasugrel-treated patients [19].…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Prasugrel achieves a faster and more profound inhibition of ADP-induced platelet aggregation than clopidogrel, due to a greater generation of its active metabolite [8]. After a loading dose, concentrations of prasugrel's active metabolite rapidly rise in the plasma, with peak concentration reached at 30 min [9], compared to 60 min for clopidogrel [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, its antiplatelet effect is greater and achieved more rapidly because of different pathways in metabolizing the pro-drug, which are desirable characteristics in conditions such as STEMI and NSTEMI [67,68]. The TRI-TON-TIMI 38 trial assessed the performance of both antiplatelet agents in patients with ACS and demonstrated improved platelet inhibition and clinical outcomes with prasugrel compared with clopidogrel, in particular in patients with STEMI or diabetes, or those undergoing stent implantation [69][70][71][72][73].…”
Section: Antiplatelet Therapymentioning
confidence: 99%